Efektivitas Ekstrak Bawang Putih dan Bawang Hitam dalam Menghambat Pertumbuhan Candida albicans - Ni Made Widia Sasmita Indraswari; Dyah Indartin Setyowati; Zahreni Hamzah (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Antifungal drugs that already exist have several side effects, so it needs to be developed a new drug from natural ingredients. Garlic and black garlic are known to have organosulfur compounds that can be used as an antifungal. This study aimed to determine the effectiveness of garlic (A. sativum) and black garlic extract in inhibiting the growth of Candida albicans. This study used 3 groups, namely control group, the garlic (A. sativum) extract group and the black garlic extract group by using concentration 100%, 75%, 50%, and 25% with 3 times replication. Extraction using maceration method with 96% ethanol solvent, while the antifungal test using disk diffusion method. antifungal effect is determined by calculating the inhibition zone formed on Sabouraud Dextrosa Agar (SDA) media after incubating for 24 hours. The results of Kruskall-Wallis test showed a significance value (p <0.05) which means there were differences in all groups. In the Mann-Whitney test showed a significance value (p >0.05) which means there are no significant differences between treatment groups. In conclusion, garlic extract is more effective compared to black garlic extract but the difference is not significant.